Clusters of risk factors for chronic non-communicable diseases in community health workers (Revista Contexto & Saúde, 2025)
This study aimed to estimate the prevalence ofclustersof behavioral risk factors for Chronic Diseases Do NotCommunicable Diseases (NCDs), as well as associated factors in Community Health Agents (CHAs). This is a census, cross-sectional, analytical study, derived from a research project entitled Working and health conditions of CHAs in northern Minas Gerais: a longitudinal study, carried out in the city of Montes Claros, MG. The dependent variable wassimultaneous presence, orclusters of three or more behavioral risk factors for NCDs. The definition of associated variables was performed after Poisson multiple regression analysis with robust variance. A total of 675 CHWs participated in the study. Of these, 57.6% (n=389) presented at least three simultaneous risk factors for NCDs, the most prevalent being low fruit consumption, physical inactivity and excessive consumption of soft drinks. The variables that were associated with the cluster of behavioral factors were age greater than or equal to 37 years (PR=0.87; 95%CI=0.81-0.94; p=0.001), perception of poor health status (PR=1.08; 95%CI=1.00-1.16; p=0.037) and presence of hypertension (PR=1.17; 95%CI=1.06-1.30; p=0.001). It is concluded that the prevalence of three or more risk factors for NCDs in CHAs was high, and that sociodemographic and clinical factors are associated with the outcome investigated. Considering the results recorded, health services should provide differentiated care policies for CHAs, seeking to prevent behavioral factors that can increase morbidity and mortality due to NCDs.
Keywords: Community health agents; Non-communicable diseases; Risk factors; Health-related behaviors